The reading and writing from mild intellectual disability - Galindo Ascanio, Geydi Katherine; Nieto Henao, Tatiana Marcela; Pinzón Gonzalez , Jully Paola (Rastros Rostros, 2023)
Intellectual disability is currently a challenge for the educational community due to the lack of knowledge of the characteristics and needs of the population with this diagnosis, being necessary to update issues of inclusion to identify the various factors that influence the learning difficulties present in this population. The research carried out is aimed at studying learning processes and eliminating educational gaps in the classroom. In this descriptive research with a quantitative approach, the objective was to identify the main learning difficulties in the reading and writing process of 15 fourth and fifth grade students with a diagnosis of mild intellectual disability between 8 and 12 years of age. district school of Bogotá, through a pedagogical characterization with the application of a booklet that evaluated the components of the language and two checklists, finding that the main difficulties are the absence of connectors with 100 %, lack of punctuation marks in 93, 33 %, incorrect use of capital letters in 86.67 %, addition of letters and/or words in 80 %, confusion and omission in the order of letters and/or words in 73.33 %; the inappropriate use of vocabulary with 66.67 %.